Reflections of stress in US abortion narratives. (September 2020) - Sperlich, Mickey; Ely, Gretchen E; Rouland, Rebecca S; Walters, Connor A; Carwile, Max
A trauma-informed, thematic analysis that identified stress-related themes evident in 39 personal abortion narratives from the Tennessee Stories Project in the United States is presented in this paper. Using the Braun and Clarke model of thematic analysis, guided by the trauma-informed social work framework, researchers examined these narratives to identify stress related themes. Findings: An overall theme of stress and traumatic stress was found to be present throughout the abortion narratives. These themes were categorized into subthemes, including: (a) existing life stressors preceding the abortion experience, (b) stressors while trying to access abortion services, (c) stressors while obtaining abortion services, and (d) stressors arising after the procedure. Applications: These results suggest that stress and traumatic stress were reflected in these abortion narratives throughout the abortion seeking experience. This finding supports the need for social work practice responses that are designed to address and eliminate stress during the process of seeking and obtaining an abortion in the United States. A trauma-informed framework is recommended for guiding social work education about abortion, social worker interactions with clients who are seeking abortions, and the development of abortion policy in the United States in order to better align the abortion seeking experience with the principles of trauma-informed care.